Pengaruh Transparansi, Akuntabilitas, dan Literasi Zakat terhadap Preferensi Muzakki Dalam Memilih Distribusi Zakat - Nugroho, Anton Priyo; Syam, Fahmi; Semmawi, Ramli; Sasono, Heri; Hasibuan, Kalijunjung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The process of collecting, managing and distributing zakat is ideally carried out by the Zakat Management Organization (OPZ). In Indonesia there are two types of OPZ which are recognized by law (UU No. 23 of 2011 concerning Zakat Management), the Amil Zakat Agency (BAZNAS) and the Amil Zakat Institution (LAZ). This research aims to determine the influence of transparency, accountability and zakat literacy on muzakki preferences in choosing zakat distribution. The population and sample in this study were muzakki who had paid zakat at the Amil Zakat Institution using a probability sampling technique: simple random which was successfully obtained as many as 180 respondents in this study. The results of this research show that the variables of transparency, accountability and zakat literacy influence muzakki preferences in choosing zakat distribution. Keywords: Transparency, Accountability, Zakat Literacy, and Muzakki Preferences